HUBUNGAN KUALITAS TIDUR DENGAN TINGKAT KEBUGARAN JASMANI PADA SISWA KELAS IX DI UPT SMP NEGERI 1 TUBAN - Azaria Farahma Miska; Vega Candra Dinata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Adolescent sleep quality has declined due to academic pressure, digital technology use, and circadian rhythm changes during puberty, which directly contributes to decreased students’ physical fitness. Previous studies have attempted to examine the relationship between sleep and adolescent physical performance by measuring only total sleep duration. However, this approach is considered insufficiently comprehensive because it neglects important dimensions such as sleep latency, efficiency, and consistency, and rarely employs standardized national physical fitness instruments. Based on chronobiology theory and exercise physiology, sleep plays a crucial role in regulating growth hormones, muscle recovery, and cardiorespiratory capacity. In this context, this study integrates the Pittsburgh Sleep Quality Index (PSQI) as a multidimensional measure of sleep quality with the Indonesian Physical Fitness Test (TKJI) in a population of Grade IX students. The aim of this study is to analyze the relationship, the strength of the correlation, and the most dominant sleep quality components influencing physical fitness. This research employed a quantitative correlational design with a cross-sectional approach. The sample consisted of 114 Grade IX students from UPT SMP Negeri 1 Tuban, selected using proportional stratified random sampling. Data were analyzed using Pearson correlation analysis. The results show a significant negative correlation between sleep quality and physical fitness (r = -0.678; p = 0.000), with a contribution of 45.9%. Among all components, sleep latency and sleep efficiency were identified as the most dominant factors affecting cardiorespiratory endurance. These findings indicate that poorer sleep quality is associated with lower physical fitness levels among adolescents. In conclusion, sleep quality is a significant determinant of adolescent physical fitness and requires serious attention within educational and health policies. Improving sleep hygiene and managing academic workload may play an important role in enhancing students’ physical performance and overall well-being.